The Effect of Buy One Get One (BOGO) Promotion and Social Media Strategy on the Perception of Value and Consumer Satisfaction of Islamic Film Tickets at Cinema XXI Solo Grand Mall: A Case Study of Students in Surakarta - Nur ‘Ainie Diena Khanifah; Muhammad Sholahuddin (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the effects of Buy One Get One (BOGO) promotions and social media strategies on perceived value and consumer satisfaction for Islamic film tickets at Cinema XXI Solo Grand Mall, focusing on students in Surakarta. Using a quantitative approach, data were collected from 179 respondents through purposive sampling and analyzed via Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. Results indicate that BOGO promotions significantly increase consumer satisfaction, while social media strategies have no direct significant effect. Both BOGO promotions and social media strategies, however, positively influence perceived value, which partially mediates their impact on satisfaction. This research contributes to understanding how promotional tactics and digital marketing interact to shape consumer perceptions in the niche Islamic film market and provides actionable insights for cinema managers to optimize marketing strategies targeting student audiences.